2017
DOI: 10.1186/s13011-017-0118-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional beliefs and risk minimizing beliefs among Thai healthcare workers in Maharaj Nakorn Chiang Mai hospital: its association with intention to quit tobacco and alcohol

Abstract: BackgroundIndividual health beliefs are likely to play a key role in how people respond to knowledge and information about the potential harm from smoking and alcohol abuse. The objectives of the study were to 1) explore whether functional beliefs and risk minimizing beliefs were associated with intention to quit smoking and confidence to quit smoking and 2) explore whether functional beliefs and risk minimizing beliefs were associated with intention to quit alcohol drinking and confidence to quit alcohol drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Secondly, risk-minimizing beliefs are quite fragile and can be altered easily by providing negative information and appropriate feedback [34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Secondly, risk-minimizing beliefs are quite fragile and can be altered easily by providing negative information and appropriate feedback [34].…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of health beliefs about alcohol drinking was evaluated using a nineitem questionnaire derived from previous studies [37,38]. The Thai version has been used and published in previous literature [34]. The first five items were regarding the individual functional beliefs of alcohol use, whereas the latest four items were regarding the individual risk-minimizing beliefs about the risk of alcohol use.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study that investigated the beliefs of nurses in Northern Thailand explored postpartum care and found discrepancies between nurses’ beliefs and contemporary evidence-based practices (Kaewsarn, Moyle, & Creedy, 2003). Aside from this, the only recent study exploring beliefs of Thai health professionals was with regard to tobacco cessation (Jiraniramai et al, 2017). The authors concluded that there was a need to undertake further descriptive studies in regions where traditional cultural practices remain widespread to establish the nature of health professional beliefs, particularly in the context of widespread social and health policy change.…”
Section: Literature Reviewmentioning
confidence: 99%